'Green barriers' for air pollutant capture: Leaf micromorphology as a mechanism to explain plants capacity to capture particulate matter. (1st November 2021) - Redondo-Bermúdez, María del Carmen; Gulenc, Idris Tugrul; Cameron, Ross W.; Inkson, Beverley J.
Abstract: Finding ways to mitigate atmospheric particulate matter (PM) is one of the key steps towards fighting air pollution and protecting people's health. The use of green infrastructure is one option that could help improving urban air quality and promoting more sustainable cities. Detailed knowledge of how plants capture particulate matter can support plant selection for this purpose. Previous studies have primarily focused on 2D techniques to assess the micromorphology of plant leaves. Here, 3D optical profilometry and SEM imaging (2D) are used to quantify leaf roughness and other micromorphological leaf traits of three contrasting plant species ( Hedera helix 'Woerner', Thuja occidentalis ' Smaragd', and Phyllostachys nigra ) located within a mixed-species green barrier. These techniques have allowed us to identify the relative distribution of adhered atmospheric PM with respect to the surface topography of leaves, with high spatial resolution. Leaf surface roughness did not show a direct relationship with PM deposition; however, the descriptors width, depth and frequency of the grooves are important to explain PM capture by the leaves. Additionally, the presence of wax on leaves was relevant for PM adherence. All species captured PM, with their overall PM capture efficiency ranked from highest to lowest as follows: Thuja occidentalis > Hedera helix > Phyllostachys nigra . All green barrier species contributed to air quality improvement, through PM capture, regardless of their location within the barrier. Having multiple species in a green barrier is beneficial due to the diverse range of leaf micromorphologies present, thus offering different mechanisms for particulate matter capture. Graphical abstract: Image 1 Highlights: Leaf surface roughness characteristics that explain particulate matter (PM) capture by plants include width, depth, and frequency of surface grooves. Hedera helix leaf surface roughness is effective for PM1 and PM2.5 capture due to optimal groove size and frequency. Wax presence is a key micromorphological mechanism for PM capture for Thuja occidentalis. Phyllostachys nigra showed the lowest comparative PM load, but it is important for PM1 capture and pollution deflection as a structural plant. A mixed-species green barrier provides multiple opportunities to capture atmospheric PM by the diverse leaf micromorphologies.